A Narrative Review on Tuberculosis Disease Transmission, Treatment, Prevention, Emergency Care, and Vaccine Allocation in Second Highest Populated Country (India) - Jyoti; Ravinder Kaur (International Journal of Emergency and Trauma Nursing and Practices, 2024)
Tuberculosis, an airborne illness caused by Mycobacterium tuberculosis, is a highly contagious disease primarily impacting the lungs, though it can also affect other body parts, excluding hair and nails. There are two main types of tuberculosis: pulmonary tuberculosis (PTB), which targets the lungs, and extrapulmonary tuberculosis (EPTB), which involves other areas such as lymph nodes, bones, joints, and the nervous system. The theme for World Tuberculosis Day in 2024 is ‘Yes! We can end TB’, emphasizing the global commitment to eradicate this lethal disease through continuous efforts and educational campaigns.
Keywords: Tuberculosis; airborne disease; elimination; lymph node; pulmonary